Enhancing Performance of Breast Ultrasound in Opportunistic Screening Women by a Deep Learning-Based System: A Multicenter Prospective Study - Zhao, Chenyang; Xiao, Mengsu; Ma, Li; Ye, Xinhua; Deng, Jing; Cui, Ligang; Guo, Fajin; Wu, Min; Luo, Baoming; Chen, Qin; Chen, Wu; Guo, Jun; et al. (Frontiers in Oncology, 2022)
Purpose To validate the feasibility of S-Detect, an ultrasound computer-aided diagnosis (CAD) system using deep learning, in enhancing the diagnostic performance of breast ultrasound (US) for patients with opportunistic screening-detected breast lesions. Methods Nine medical centers throughout China participated in this prospective study. Asymptomatic patients with US-detected breast masses were enrolled and received conventional US, S-Detect, and strain elastography subsequently. The final pathological results are referred to as the gold standard for classifying breast mass. The diagnostic performances of the three methods and the combination of S-Detect and elastography were evaluated and compared, including sensitivity, specificity, and area under the receiver operating characteristics (AUC) curve. We also compared the diagnostic performances of S-Detect among different study sites. Results A total of 757 patients were enrolled, including 460 benign and 297 malignant cases. S-Detect exhibited significantly higher AUC and specificity than conventional US (AUC, S-Detect 0.83 [0.80–0.85] vs. US 0.74 [0.70–0.77], p < 0.0001; specificity, S-Detect 74.35% [70.10%–78.28%] vs. US 54.13% [51.42%–60.29%], p < 0.0001), with no decrease in sensitivity. In comparison to that of S-Detect alone, the AUC value significantly was enhanced after combining elastography and S-Detect (0.87 [0.84–0.90]), without compromising specificity (73.93% [68.60%–78.78%]). Significant differences in the S-Detect’s performance were also observed across different study sites (AUC of S-Detect in Groups 1–4: 0.89 [0.84–0.93], 0.84 [0.77–0.89], 0.85 [0.76–0.92], 0.75 [0.69–0.80]; p [1 vs. 4] < 0.0001, p [2 vs. 4] = 0.0165, p [3 vs. 4] = 0.0157). Conclusions Compared with the conventional US, S-Detect presented higher overall accuracy and specificity. After S-Detect and strain elastography were combined, the performance could be further enhanced. The performances of S-Detect also varied among different centers.